The only mystery of quantum mechanics - Pabjan, Tadeusz (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2013)
The double slit experiment is a relatively simple physical test that can be useful for demonstrating the corpuscular-wave dualism of light and matter, which is the supreme mystery of the whole quantum physics. A particular riddle here is especially the mechanism responsible for the formation of a interference pattern in a situation when single quantum objects pass through the experimental setup. In the article the main idea of the experiment is discussed and two possible explanations of its results are briefly shortly presented: the view of the Copenhagen school and the de Broglie-Bohm’s pilot wave theory.